Stability and Function of Hippocampal Mossy Fiber Synapses Depend on Bcl11b/Ctip2 - De Bruyckere, Elodie; Simon, Ruth; Nestel, Sigrun; Heimrich, Bernd; Kätzel, Dennis; Egorov, Alexei V.; Liu, Pentao; Jenkins, Nancy A.; Copeland, Neal G.; Schwegler, Herbert; Draguhn, Andreas; Britsch, Stefan (Frontiers in Molecular Neuroscience, 2018)
Structural and functional plasticity of synapses are critical neuronal mechanisms underlying learning and memory. While activity-dependent regulation of synaptic strength has been extensively studied, much less is known about the transcriptional control of synapse maintenance and plasticity. Hippocampal mossy fiber synapses connect dentate granule cells to CA3 pyramidal neurons and are important for spatial memory formation and -consolidation. The transcription factor Bcl11b/Ctip2 is expressed in dentate granule cells and required for postnatal hippocampal development. Ablation of Bcl11b/Ctip2 in the adult hippocampus results in impaired adult neurogenesis and spatial memory. The molecular mechanisms underlying the behavioral impairment remained unclear. Here we show that selective deletion of Bcl11b/Ctip2 in the adult mouse hippocampus leads to a rapid loss of excitatory synapses in CA3 as well as reduced ultrastructural complexity of remaining mossy fiber boutons. Moreover, a dramatic decline of LTP of the dentate gyrus-CA3 projection is caused by adult loss of Bcl11b/Ctip2. Differential transcriptomics revealed the deregulation of genes associated with synaptic transmission in mutants. Together, our data suggest Bcl11b/Ctip2 to regulate maintenance and function of mossy fiber synapses in the adult hippocampus.